2021
DOI: 10.1017/s1368980021000720
|View full text |Cite
|
Sign up to set email alerts
|

Does coffee, tea and caffeine consumption reduce the risk of incident breast cancer? A systematic review and network meta-analysis

Abstract: Objective: We aimed to evaluate the association between coffee and/or tea consumption and breast cancer (BC) risk among premenopausal and postmenopausal women and to conduct a network meta-analysis. Design: Systematic review and network meta-analysis. Setting: We conducted a systematic review of electronic publications in the last 30 years to identify case–control studies or prospective cohort studies that evaluated the effects of coffee and tea intake. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Additionally, the summary results of all cohort studies or case-control studies showed no association of black tea intake with breast cancer risk ( 11 ). A network meta-analysis that included 45 cohort and case-control studies found that tea drinking was not related to a lower overall breast cancer risk in postmenopausal women ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the summary results of all cohort studies or case-control studies showed no association of black tea intake with breast cancer risk ( 11 ). A network meta-analysis that included 45 cohort and case-control studies found that tea drinking was not related to a lower overall breast cancer risk in postmenopausal women ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an unclear consensus in the epidemiological studies on whether tea consumption is beneficial to population health, especially for cancer (8). Several meta-analyses showed that tea was not related to breast cancer risk (9)(10)(11)(12)(13), some studies reported an inverse effect against breast cancer (14)(15)(16), and several studies showed a positive association (17). The reliability of these findings can be easily influenced by cross-sectional design, small sample size, insufficient follow-up period, or different reference groups.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis including 3,323,288 participants showed that heavy tea consumption has a preventing effect against ER-BC, especially in the post-menopausal women. Therefore, tea was considered to be a potentially useful dietary protectant for preventing BC and a recommended dose was ≥5 cups/day ( 23 ).…”
Section: Epidemiological Evidence Of Anticarcinogenic Effects Of Tea ...mentioning
confidence: 99%